Penetapan Kadar Fenol Total Dan Aktivitas Antioksidan Dari Ekstrak Etanol Kulit Kentang (Solanum Tuberosum L.) - Vinda Maharani Patricia; Tasya Luthfiyyah; Livia Syafnir (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Indonesia is one of the countries with a diversity of plants, one of which is the potato plant (Solanum tuberosum L.). Some compounds found in potato peels have pharmacological activities, one of which is antioxidants. This study aimed to determine the total phenol content and the antioxidant activity produced by potato peel ethanol extract. The methods for total phenolic content used the Folin-Ciocalteu method and the DPPH(2,2-diphenyl-1-picrylhydrazyl) method for antioxidant activity. The result obtained from this study was that the total phenol content in ethaol extract of potato peel was 152.9 mg GAE / g extract and antioxidant activity showed with IC50 value was 30,339 ppm, which means that potato peel ethanol extract has a very strong antioxidant activity.